You want to multiply each term in the first set of parentheses by each term in the second set of parentheses:
2x * 5x = 10x^2
2x * 1 = 2x
3 * 5x = 15x
3 * 1 = 3
Add it all together to get: 10x^2 + 17x + 3
2007-01-25 06:06:25
·
answer #1
·
answered by Billy Nostrand 3
·
0⤊
0⤋
Well, this isn't an equation, just an expression to multiplicate and simplify.
(2x+3) (5x+1) =
(2x * 5x) + (2x * 1) + (3 * 5x) + (3 * 1) =
10x^2 + 2x + 15x + 3 =
10x^2 + 17x + 3
You forgot to multiply the x's in 2x * 5x.
2007-01-25 06:13:33
·
answer #2
·
answered by jcastro 6
·
0⤊
0⤋
wrong
10 x^2 + 2x+15x+3 = 10x^2 + 17x + 3
2007-01-25 06:08:08
·
answer #3
·
answered by sm bn 6
·
0⤊
0⤋
(2x + 3)(5x + 1) = 10x^2 + 2x + 15x + 3
= 10x^2 + 17x + 3
2007-01-25 06:07:18
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
(2x+3) (5x+1) use FOIL
10x^2+2x+15x+3
10x^2+17x+3
No. the 10x should be 10x^2
2007-01-25 06:40:39
·
answer #5
·
answered by yupchagee 7
·
0⤊
0⤋
Almost...
(2x)(5x) = 10x^2
So
10x^2 + 2x + 15x + 3
or 10x^2 + 17x + 3
2007-01-25 06:08:14
·
answer #6
·
answered by MamaMia © 7
·
0⤊
0⤋
No!
(2x+3) (5x+1)
10x^2+2x+15x+3
10x^2+10x+3
you forgot that 2x*5x = 10x^2
2007-01-25 06:06:43
·
answer #7
·
answered by 7
·
1⤊
1⤋
(2x+3) (5x+1) 2x * 5x= 10x^2
10x^2+15x+2x+3
10x^2+17x+3
2007-01-25 06:09:44
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
no....
10x squared +2x+15x+3
so...
(10x^2)+17x+3
2007-01-25 06:08:23
·
answer #9
·
answered by Maria B 3
·
0⤊
0⤋
the 10x should be 10x², so it's
10x²+17x +3
2007-01-25 06:08:57
·
answer #10
·
answered by bequalming 5
·
0⤊
0⤋